Extractive Spectrophotometric Determination of copper with p-Methylisonitrosoacetophenonehydrazone - Lokhande, R.S.; Jaywant, A.S. (Asian Journal of Chemistry, 2010)
A simple and rapid extractive spectrophotometric method for the determination of Cu(II) is studied. The complex formed between Cu(II) and p-methylisonitrosoacetophenonehydrazone is extracted into chloroform from aqueous solution of pH 7.0. The extracted species has an absorption maximum at 510 nm and obeys Beer's law over a range of 0.1–1.0 μg mL–1 of Cu(II); the molar absorptivity being 6.28 x 103 L mole–1 cm–1. Interference from foreign ions has also been studied.